Casanare bonanza resources oil has reduced by law 1530, 2012 (2013)
Colombia is a producer of hydrocarbons, especially oil that focuses on certain regions of the country, for scans that have been performed with positive results for both the central government and the region where production. With the birth of the act 05 of 2011 takes a radical turn to the distribution of the resources generated by oil exploration in Colombia. In 2012 this distribution is formalized through 1530, 2012 law that standardizes the distribution of the royalties.